ANALISIS FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG - Alexander, Timotius; Salim, Susanto (Jurnal Paradigma Akuntansi, 2024)
The aims of this research is to discover the influence of earning volatility, liquidity, asset structure and firm size towards debt policy on property, real estate and building construction companies listed on the Indonesia Stock Exchange in 2018-2020. The method in selecting the sample is using purposive sampling method and the selected sample is 31 companies. This study uses secondary data and data processing in a way by multiple regression analysis assisted by using Eviews software version 12 and Microsoft Excel version 2016. The results of this research indicate that firm size has a significant influence on debt policy while earnings volatility, liquidity and asset structure do not have a significant influence on debt policy.